Azelaic acid in dermatological treatment - current state of knowledge - Radomir Reszke; Jacek Szepietowski (Termedia Publishing House, 2016)
Azelaic acid (AZA) is a naturally occurring substance produced by Malassezia furfur which exerts various effects on the skin. Azelaic acid has antibacterial, anti-inflammatory, keratolytic, comedolytic, sebostatic and tyrosinase-inhibiting properties. Topical application of AZA as 20% cream or 15% gel is a well-established therapeutic method in various common dermatoses, mainly acne vulgaris, rosacea and disorders associated with hyperpigmentation. Azelaic acid is used as a component of chemical peels as well. The paper summarizes the most relevant issues concerning AZA application in dermatological treatment based on current knowledge.